Risk mapping for HPAI H5N1 in Africa - Improving surveillance for virulent bird flu: Final report and maps - Stevens, K.B.; Costard, Solenne; Métras, Raphaëlle; Theuri, Wachira; Hendrickx, Saskia C.J.; Pfeiffer, Dirk U. (International Livestock Research Institute, 2010)
More than 85 percent of households in rural Africa raise poultry for food, income, or both, and many people live in close contact with their birds. The possibility of an epidemic of highly pathogenic avian influenza (HPAI) H5N1 is therefore a major concern. Since 2006 bird fl u has been introduced into at least 11 countries in Africa, and over 600 outbreaks reported.